Students’ Perceptions on Characteristics of Attributes of an Effective EFL Teacher (A Survey Study at a Multimedia Class of a Vocational High School in Ciamis) - Roni Sujana (Universitas Galuh, 2023)
This study revealed students’ perceptions on characteristics of attributes of an effective EFL teacher at a multimedia class of a vocational high school in Ciamis/ Indonesia in academic year of 2020-2021. The purposes were to figure out the students’ perceptions on characteristics among attributes of an effective EFL teacher at a vocational high school and to figure out the dominant characteristics among attributes of an effective EFL teacher at a vocational high school based on students’ perceptions. A survey study was used as a research design; and thus 25 students at class XI- Multimedia were selected as the participants. The questionnaires and the interview were used to collect the data. Triangulation analysis was used by the writer to triangulate the results of the questionnaires and the interview. The findings showed that the students perceived their teacher had five attributes of characteristics on effective EFL teacher. Those five attributes of characteristics were rapport, delivery, fairness, knowledge and credibility, as well as organization and preparation. The findings also showed that those attributes were the dominant characteristics among attributes of an effective EFL teacher at a vocational high school based on students’ perceptions. However, there was not dominant attribute of effective EFL teacher on organization and preparation characteristics. The conclusion indicated that an effective EFL teacher must have five attributes of characteristics. It also pointed out that those five attributes of characteristics were dominant characteristics of effective EFL teacher at vocational high school emerged based on students’ perceptions. It is suggested for the next researchers to apply performance assessment to measure the students’ improvements on English abilities, achievement, and academic performance.